2018
DOI: 10.1186/s10194-018-0909-4
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and cluster headache – the common link

Abstract: Although clinically distinguishable, migraine and cluster headache share prominent features such as unilateral pain, common pharmacological triggers such glyceryl trinitrate, histamine, calcitonin gene-related peptide (CGRP) and response to triptans and neuromodulation. Recent data also suggest efficacy of anti CGRP monoclonal antibodies in both migraine and cluster headache. While exact mechanisms behind both disorders remain to be fully understood, the trigeminovascular system represents one possible common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 237 publications
(271 reference statements)
1
58
2
3
Order By: Relevance
“…Likewise, imaging studies have also shown that the hypothalamic nuclei are activated during the pain phase of cluster headache attacks . The cyclic nature and circadian predictability of cluster headache is consistent with the pacemaking functions of hypothalamic nuclei …”
Section: Introductionmentioning
confidence: 78%
“…Likewise, imaging studies have also shown that the hypothalamic nuclei are activated during the pain phase of cluster headache attacks . The cyclic nature and circadian predictability of cluster headache is consistent with the pacemaking functions of hypothalamic nuclei …”
Section: Introductionmentioning
confidence: 78%
“…Migraine and cluster headache (CH), though clinically distinguishable by ICHD‐3 criteria, share a common pathophysiology: the trigeminovascular pathway . Trigeminal afferents are pseudo‐unipolar neurons with cell bodies forming the trigeminal ganglion (TG) where neurons interact with the surrounding satellite glial cells and other cell types .…”
Section: Introductionmentioning
confidence: 99%
“…Great challenges remain in managing migraine and CH, since these are complex neurovascular pain syndromes. Based on the attack frequency or cluster period, migraine and CH can be categorized as episodic or chronic . Many clinically effective preventive medications are used off‐label and each demonstrates a unique adverse effect (AE) profile, possibly impacting medication adherence and leading to headache chronification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations